Evolution of paleogene basins in northwestern southamerica: tracking the change from caribbean to nazca subduction (2012)
In the northern Andes, inversion of mesozoic extensional structures, have controlled the location of synorogenic successions and dispersal of detritus since Paleocene time. Detailed geologic mapping, tectosedimentological studies using provenance (petrography, heavy minerals, geochronology), biostratigraphy and termogeochronological data, conducted in several basins with paleogene strata across the present Eastern Cordillera, southern Llanos Basin and the Perijá Range, that reactivation of former normal faults broke the single Upper Cretaceous basin into different depocenters that migrates through the Paleogene period......